The Effect of Self Regulated Learning on Learning Outcomes of Mathematics Education Students in Online Lectures - Fitriyani Hali (JME (Journal of Mathematics Education), 2021)
Self Regulated Learning during online lectures plays a very important role in the success of student learning. Activities to determine the effect of Self Regulated Learning on student educational professional learning outcomes is the purpose of this study. The research method used in this study is a survey method using simple linear regression analysis. The sample was obtained using a saturated sample, namely the entire population of 25 students of the mathematics education study program at Ninebelas November Kolaka University in the odd semester of the 2020/2021 academic year. Data collection was carried out by providing self regulated learning questionnaires and essay tests on learning outcomes of the educational profession. Data analysis was carried out using the SPSS program consisting of descriptive analysis analysis, classical assumption test and research hypothesis testing. Classical assumption test in the form of normality test and linearity test. The conclusion of the research that has been carried out is that there is a significant positive effect between self regulated learning on the learning outcomes of the educational profession in students of the mathematics education study program. The large contribution of self regulated learning to the learning outcomes of the educational profession is 23.5% and 76.5% is contributed by variables other than self regulated learning.